RANCANG BANGUN ROBOT BERODA PEMADAM API MENGGUNAKAN ARDUINO UNO REV.1.3 - Markus Dwiyanto Tobi (Electro Luceat, 2015)
Frequent fire accident has caused many casualties and property losses . There is a risk that must be borne by the time firefighters extinguish a fire in a room such as falling objects falling from the roof of a building or fire getting bigger . In this final project will be made prototypes of fire fighting robot by taking an example of a simulated fire in the arena . This robot  designed to operate using four types of sensors , including a sound sensor activation to signal the start-up time in activating the robot , ultrasonic sensor for distance detection , Uvtron sensor detection for the presence or absence of the presence of fire , and pie detects line sensor for the presence of fire. Things to be obtained from the design of a prototype robot is a robot fire extinguisher fire extinguisher can scour the room in an attempt to locate the fire and extinguish it . It can be concluded that the fire fighting robot prototype can be used as a basis if you want to make an actual fire fighting robot .